Radioligand Binding Assays in the Drug Discovery Process: Potential Pitfalls of High Throughput Screenings - Noël, François; Mendonça-Silva, Dayde Lane; Quintas, Luis Eduardo M. (Arzneimittelforschung, 2001)
Radioligand binding assays evaluating directly the ability of a drug to interact with a defined molecular target is part of the drug discovery process. The need for a high throughput rate in screening drugs is actually leading to simplified experimental schemes that increase the probability of false negative results. Special concern involves voltage- gated ion channel drug discovery where a great care is required in designing assays because of frequent multiplicity of (inter-acting) binding sites. To clearly illustrate this situation, three different assays used in the academic drug discovery program of the authors were selected because they are rich of intrinsic artifacts: (I) (20 mmol/1 caffeine almost duplicated [3H]ryanodine binding (89 % higher than control) to rat heart microsomes at 0.3 µmol/l free calcium but did not exert any effect when using a high (107 µmol/l) free calcium, as mostly used in ryanodine binding assays; (II) An agonist for the ionotropic glutamate receptor of the kainate type can distinctly affect [3H]kainate binding to chicken cerebellum membranes depending on its concentration: unlabelled kainic acid perse either stimulated about 30 % (at 50–100 nmol/l), had no effect (at 200 nmol/l) or even progressively decreased (at 0.3-2 µmol/l) the binding of 5 nmol/l [3H]kainate, emphasizing the risk of using a single concentration for screening a drug; (III) In a classical [3H]flunitrazepam binding assay, the stimulatory effect of a GABA (γ- aminobutyric acid) agonist was only observed when using extensively washed rat brain synaptosomes (10µmol/l GABA increased flunitrazepam binding by 90 %). On the other hand, the inhibitory effect of a GABA antagonist was only observed when using crude synaptosomes (10 µmol/l bicuculine reduced [3H]flunitrazepam binding by 40 %).It can be concluded that carefully designed radioligand assays which can be performed in an academic laboratory are appropriate for screening a small number of drugs, especially if these are potential hits because of their rational design. Therefore, the low throughput rate could be partially balanced by a higher performance when compared to what is done in a robotic high throughput screening where simplification of assay conditions can lead to false negative results.
Keywords: γ-Aminobutyric acid agonist; Benzodiazepine; Caffeine; Drug Screening; Kainic acid; Radioligand binding; Ryanodine